Survival strategies for the microbiome in a vent-dwelling glass sponge from the middle Okinawa Trough - Li, Yu-Hang; Yang, Ming; Wei, Tao-Shu; Chen, Hua-Guan; Gong, Lin; Wang, Yong; Gao, Zhao-Ming (Frontiers in Microbiology, 2025)
The adaptive mechanisms of sponge microbiomes to harsh deep-sea environments, including hydrothermal vents and cold seeps, remain unclear. Here, we used metagenomics to investigate the microbiome of an undescribed vent-dwelling glass sponge from the middle Okinawa Trough, probably representing a novel species within the family Bolosominae. Eleven high-quality prokaryotic metagenome-assembled genomes (MAGs) were retrieved, none assignable to known species, with two representing new genera. Dominant MAGs included sulfur-oxidizing bacteria (SOB) and ammonia-oxidizing archaea, followed by methane-oxidizing bacteria (MOB) and nitrite-oxidizing bacteria. Global distribution analysis suggested that most MAGs were sponge-specific symbionts. Comparative genomics revealed functional redundancy among SOB and early-stage genome reduction in a unique MOB lineage. Additionally, a total of 410 viral contigs were identified, most exhibiting a lytic lifestyle and forming distinct clades from known viruses. Our work expands understanding of the diversity and novelty of deep-sea sponge-associated prokaryotes and viromes, and suggests their niche adaptation to hydrothermal fluid environments.